Quality of Restructured Buffalo Meat Fillets extended with Hydrated Barley - Ahmad, S.R.; Sharma, B.D.; Irshad , A. (Journal of Meat Science, 2014)
The study was aimed at optimizing level of hydrated barley flour in restructured buffalo meat fillets. The hydrated barley flour at three levels viz. 8, 10, and 12 percent was used as extender replacing lean meat in the formulation of control restructured buffalo meat fillets. The extended fillets were evaluated for various physico-chemical and sensory properties and compared with the control. The cooking yield increased with barley flour extension and at 12 percent level, it was significantly higher (P
Keywords: barley flour; fillets; hydrated; production cost; restructured; sensory scores